The Effect of Human Resource Information Systems (HRIS) and Artificial Intelligence on Defense Industry Performance - Tessa Handra; Veera Pandiyan Kaliani Sundram (Pandawan Sejahtera Indonesia, 2023)
The purpose of this research is to analyze the effect of the Human Resource Information System (HRIS) on the performance of the defence industry and the influence of artificial intelligence on the performance of the defence industry during the disruption era. This study uses a quantitative research approach. The samples processed were 160 defence industry employees. The primary data collection technique is done by distributing questionnaires to respondents. The questionnaire uses a Likert scale as a measure of data. Data analysis was carried out through structural equation modelling with SmartPLS 3.0 software. The dependent variable is the employee performance variable, and the independent variable is the HRIS and job satisfaction variables. The results of data analysis in this study and the significance value obtained prove that HRIS is significantly related to employee performance. The more accurate, precise and complete the HRIS application, the higher the employee's performance in completing their work assignments and improving the process of the defence industry in making human resource decisions through systematic HRIS procedures, which include data collection, data storage, data maintenance, data retrieval, and data validation. Its strategic plan influences the progress of the defence industry in utilizing human resources quantitatively, and understanding environmental conditions can provide an overview of the future of the defence industry. Artificial Intelligence (AI) is significantly related to employee performance.